การพัฒนาสื่อวิดีโอเพื่อการเรียนรู้ผ่านยูทูบเรื่องประชากรกับการเมืองการปกครองของจังหวัดนครศรีธรรมราช สำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 3: Development of Video Media for Learning through YouTube on Population with Politics and Government of Nakhon Si Thammarat Province for Secondary School 3 - พลหาญ, ภูมิพัฒน์; คิดใจเดียว, สุนิษา; แก้วชะฎา, โสภี; ชูแก้ว, อวยพร (Journal of Humanities and Social Sciences (HUSOKKU), 2022)
Abstract The purposes of the research were 1) to development of video media for learning through YouTube on population with politics and government of Nakhon Si Thammarat province, and 2) to study video media users' satisfaction. It is a combination of development research and quantitative research that uses learning media to engage the population with politics and the government of Nakhon Si Thammarat province and a questionnaire to collect data with a sample of secondary school 3, students under the secondary education service area 12, Mueang Nakhon Si Thammarat District, Nakhon Si Thammarat Province. The statistics used in the data analysis were percentage, mean, and standard deviation. The results showed that: 1) have development of video media for learning through YouTube on population with politics and government of Nakhon Si Thammarat province divided into two parts: settlements and important people of Nakhon Si Thammarat Province. There are quality assessment results by animation experts and experts about the population with politics and government at a high level (= 4.15, =0.64), and 2) video media user satisfaction was at a high level (= 4.38, S.D.=0.56). Keywords: learning media, population, politics, governance of Nakhon Si Thammarat